THE PARADOX OF POSITIVISTIC VIEW AND PROGRESSIVE LAW OF CRIMINAL LAW ENFORCEMENT IN INDONESIA - Krismiyarsi, Krismiyarsi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
The paradox of positivistic view and progressive law in the criminal law enforcement happened because there is a difference among the law enforcement officerâ€™s view and perception.Â Our law education from the beginning until now still teaches the students the positivistic view so that after the students becoming law officers in running the law they still use positive law or positivistic view. The positivistic view is often far from the substantive justice and close to the formal justice. In order to functioning the progressive law in law enforcement especially the penal code constraint of positivistic view which rooted inside of the law enforcerâ€™s mind, therefore it is need paradigm change by fixing the law system, law education, ethics and morality of law officers , and increasing religious consciousness.Keywords: paradox, law positivism, progressive law, criminal law enforcement